2005
DOI: 10.1002/ana.20675
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of metabotropic glutamate receptor 2mRNA in T cells of ALS patients

Abstract: Metabotropic glutamate receptors alter the vulnerability of neurons to excitotoxic damage and are reported to display abnormal expression in the central nervous system of ALS patients. Using reverse transcriptase polymerase chain reaction, we investigated the mRNA expression of specific metabotropic glutamate receptor subtypes in T lymphocytes of 20 patients with sporadic ALS, compared with healthy age-matched control subjects and patients with other neurological disorders. The levels of metabotropic glutamate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 19 publications
1
23
0
1
Order By: Relevance
“…Although mGluR expression on the T cell surface has been described previously (8,(11)(12)(13)(14)(15), the mGluR expression in DC still remains unexplored. Therefore, to determine whether DC-released glutamate acts on group I mGluR via an autocrine mechanism, group I mGluR expression on the DC surface was assayed.…”
Section: Group I Mglur Are Expressed In T Cells But Not In Dcmentioning
confidence: 99%
“…Although mGluR expression on the T cell surface has been described previously (8,(11)(12)(13)(14)(15), the mGluR expression in DC still remains unexplored. Therefore, to determine whether DC-released glutamate acts on group I mGluR via an autocrine mechanism, group I mGluR expression on the DC surface was assayed.…”
Section: Group I Mglur Are Expressed In T Cells But Not In Dcmentioning
confidence: 99%
“…Moreover T-lymphocytes obtained from ALS patients have reduced mGlu2 receptor levels [48]. Expression of metabotropic glutamate receptors is also altered in ALS.…”
Section: Deregulation Of Synaptic Glutamate Pathwaysmentioning
confidence: 99%
“…Another study confirmed at the RT-PCR level the constitutive expression of mGluR5 in both resting and activated human T cells, but showed the presence of mGluR1 transcripts also in resting T cells (Chiocchetti et al 2006). Finally, RT-PCR was used to show that peripheral T cells from healthy individuals expressed transcripts for mGluR1, 2, 3 and 8, while T cells from patients with Amyotrophic Lateral Sclerosis (ALS) -a progressive and fatal neurodegenerative disease -showed reduced expression of mGluR2, but not the other mGluRs tested (Poulopoulou et al 2005a). The possible relevance of this modified mGluR2 expression in T cells to the pathology of ALS is still unknown.…”
Section: Normal Human T Cells Express Metabotropic Glutamatementioning
confidence: 99%